The DYRK1A gene is a cause of syndromic intellectual disability with severe microcephaly and epilepsy. Issue 12 (25th October 2012) - Courcet, Jean-Benoît; Faivre, Laurence; Malzac, Perrine; Masurel-Paulet, Alice; Lopez, Estelle; Callier, Patrick; Lambert, Laetitia; Lemesle, Martine; Thevenon, Julien; Gigot, Nadège; Duplomb, Laurence; Ragon, Clémence; et al.
Abstract : Background: DYRK1A plays different functions during development, with an important role in controlling brain growth through neuronal proliferation and neurogenesis. It is expressed in a gene dosage dependent manner since dyrk1a haploinsufficiency induces a reduced brain size in mice, and DYRK1A overexpression is the candidate gene for intellectual disability (ID) and microcephaly in Down syndrome. We have identified a 69 kb deletion including the 5′ region of the DYRK1A gene in a patient with growth retardation, primary microcephaly, facial dysmorphism, seizures, ataxic gait, absent speech and ID. Because four patients previously reported with intragenic DYRK1A rearrangements or 21q22 microdeletions including only DYRK1A presented with overlapping phenotypes, we hypothesised that DYRK1A mutations could be responsible for syndromic ID with severe microcephaly and epilepsy. Methods: The DYRK1A gene was studied by direct sequencing and quantitative PCR in a cohort of 105 patients with ID and at least two symptoms from the Angelman syndrome spectrum (microcephaly < −2.5 SD, ataxic gait, seizures and speech delay). Results: We identified a de novo frameshift mutation (c.290_291delCT; p.Ser97Cysfs*98) in a patient with growth retardation, primary severe microcephaly, delayed language, ID, and seizures. Conclusion: The identification of a truncating mutation in a patient with ID, severe microcephaly, epilepsy, and growth retardation, combined with its dual function in regulating the neural proliferation/neuronal differentiation, adds DYRK1A to the list of genes responsible for such a phenotype. ID, microcephaly, epilepsy, and language delay are the more specific features associated with DYRK1A abnormalities. DYRK1A studies should be discussed in patients presenting such a phenotype.